Perbandingan Kecepatan Proses Penyembuhan Luka Swiss Webster dengan Kopi Robusta dan Arabika - Arief Ristia Pangestu (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
The coffee powder as a wound treatment has been used as a traditional medicine in almost all over the world in coffee plantations. The results of wound treatment using coffee do not appear to cause complications of infection. The difficulty of treatment is the length of the wound healing process and other dangers that can be caused by these wounds, the researcher intends to conduct a literature review which aims to determine the effect of Arabica and Robusta coffee powder in shortening the duration of wound healing in male Swiss Webster mice. The method used is a literature study from national and international journals. Phenolic compounds contain Phenolic Acid, which consists of Chlorogenic Acid, 3-Caffeoylquinic Acid, and Hydrooxicinnamates, as an anti-inflammatory. The chlorogenic acid component contained in phenolic compounds for anti-inflammatory with a concentration of Green Coffea arabica is 4.1-7.9 (g / 100g), Roasted Coffea arabica 1.9-2.5 (g / 100g), Green Coffea canephora 6.1-11.3 (g / 100g) and Roasted Coffea canephora 3.3-3.8 (g / 100g). Based on the results of a literature review, the phenolic compounds of robusta coffee are higher than arabica coffee, so the process of healing robusta coffee is faster than arabica.